Smart Polymers: Basics and Applications - Baran Samui, Asit (Routledge, 2022)
The smart materials have come in to existence during conceiving the idea of materials/systems which has 4th dimension. To match the advancement in instrumentation, efforts are being done to develop materials, which are mostly smart materials. The response of stimuli responsive polymers is reversible in nature. This has developed interest among academic area, research and industrial areas as well. The challenge remains in coupling their application with non-adverse effect on the environment. To take care of all the parameter, there is requirement to understand the basics. This book is different from other book in that it explores more on polymer materials' smart behaviour covering vibration damping, thermal and electrochemical energy, sensing at trace level, biotechnology and so on. The book is distributed in 14 chapters to discuss on diverse areas. Photoresponsive polymers that can be manipulated with specific frequency of light Designing of polymers for vibration damping Smart manipulations of hydrophic and superhydrophobic polymers Biopolymers including hydrogel for smart application, drug delivery etc. Smart paints Self-healing and shape memory polymers Holography for data storage Phase change polymers and solid polymer electrolyte for thermal and electrochemical energy Molecularly imprinting polymers for sub ppm sensing and removal of undesired materials Smart textile covering the concept of advanced textiles The audience will particularly be researchers, students of higher classes and teachers involved in higher education. It will give the basics in brief and applications in details to provide total understanding to the readers.